External mandibular fixation in maxillofacial gunshot injury (Revista Argentina de Cirugía, 2026)
Maxillofacial gunshot injuries constitute a clinical challenge due to the complex anatomy and high risk of morbidity and mortality. Comminuted mandibular fractures resulting from ballistic trauma are often associated with bone loss, bacterial infection, and extensive soft tissue damage, limiting the use of open reduction with rigid internal fixation. We present the case of a 19-year-old male patient with a comminuted mandibular fracture caused by a bullet, managed with external fixation with bicortical Kirschner wires, a silicone tube, and self-curing acrylic resin. The technique enabled the stabilization of the bone fragments without the necessity for extensive approaches, thereby preserving the periosteal blood supply and reducing the risk of complications.External fixation constitutes an effective and low-cost alternative for managing complex mandibular fractures, particularly in patients with polytrauma or involvement of other tissues. This method serves as both a definitive treatment and a bridging treatment for future reconstruction.
Keywords: Wounds; Gunshot; Mandible/surgery; External Fixators